Validation of a genotype-based algorithm that identifies individuals with low, intermediate, and high serum CA19-9 levels in cancer-free individuals and in patients with colorectal cancer - Wannhoff, Andreas; Werner, Simone; Tao, Sha; Brenner, Hermann; Gotthardt, Daniel (Journal of gastrointestinal oncology, 2022)
Validation of a genotype-based algorithm that identifies individuals with low, intermediate, and high serum CA19-9 levels in cancer-free individuals and in patients with colorectal cancer
Gesehen am 26.01.2023